Spermiogenesis and Male Fertility Require the Function of Suppressor of Hairy-Wing in Somatic Cyst Cells of Drosophila. - Duan, T.; Geyer, P.K. (Genetics, 2018)
Drosophila Suppressor of Hairy-wing [Su(Hw)] protein is an example of a multivalent transcription factor. Although best known for its role in establishing the chromatin insulator of the gypsy retrotransposon, Su(Hw) functions as an activator and repressor at non-gypsy genomic sites. It remains unclear how the different regulatory activities of Su(Hw) are utilized during development. Motivated from observations of spatially restricted expression of Su(Hw) in the testis, we investigated the role of Su(Hw) in spermatogenesis to advance an understanding of its developmental contributions as an insulator, repressor, and activator protein. We discovered that Su(Hw) is required for sustained male fertility. Although dynamics of Su(Hw) expression coincide with changes in nuclear architecture and activation of coregulated testis-specific gene clusters, we show that loss of Su(Hw) does not disrupt meiotic chromosome pairing or transcription of testis-specific genes, suggesting that Su(Hw) has minor architectural or insulator functions in the testis. Instead, Su(Hw) has a prominent role as a repressor of neuronal genes, consistent with suggestions that Su(Hw) is a functional homolog of mammalian REST, a repressor of neuronal genes in non-neuronal tissues. We show that Su(Hw) regulates transcription in both germline and somatic cells. Surprisingly, the essential spermatogenesis function of Su(Hw) resides in somatic cyst cells, implying context-specific consequences due to loss of this transcription factor. Together, our studies highlight that Su(Hw) has a major developmental function as a transcriptional repressor, with the effect of its loss dependent upon the cell-specific factors.